A comprehensive assessment of Australia’s terrestrial invertebrate pet trade across physical and online marketplaces - Charlotte R. Lassaline; Adam Toomes; Erinn P. Fagan-Jeffries; Thomas Swearingen; Phillip Cassey (Biodiversity and Conservation, 2026)
The terrestrial invertebrate trade in Australia is both poorly researched and largely exempt from regulation, despite numerous conservation and biosecurity risks. To determine the extent and implications of this trade, we conducted systematic monitoring of domestic invertebrate sales between 2019 and 2025, spanning online and physical marketplaces. Platforms surveyed included social media groups, pet store websites, public classifieds, insect trading expositions, and pet stores across all Australian state and territory capital cities. Using a combination of automated web-scraping and manual field surveys, we recorded 12,839 advertisements involving at least 568 invertebrate species from 410 genera and 138 families, as well as 121 undescribed ‘pseudo-taxa’. Of the described species, 537 were native and 33 were non-native. Comparison with a previous Australian snapshot study revealed substantial species turnover, including new emerging taxa and species no longer observed in trade since 2020. Thirty-five advertised species are listed under the IUCN Red List, CITES, or Australia’s EPBC Act, including one Critically Endangered species ( Thersites mitchellae ) for which trade is strictly prohibited. We document a substantial diversity of species not previously reported in wildlife trade and provide the first survey to concurrently monitor trade within expositions, pet stores, the surface web, and social media. Our findings highlight the scale, diversity, and conservation significance of Australia’s terrestrial invertebrate trade, and demonstrate the need for improved monitoring and regulation to mitigate conservation and biosecurity risks.

From forest floor to market door: The global terrestrial invertebrate trade - Charlotte R. Lassaline; Adam Toomes; Erinn Fagan-Jeffries; Phillip Cassey (Biological Conservation, 2025)

Multi-omics reveal microbial succession and metabolomic adaptations to flood in a hypersaline coastal lagoon - Christopher Keneally; Daniel Chilton; Tyler N. Dornan; Stephen P. Kidd; Virginie Gaget; Adam Toomes; Charlotte Lassaline; Reuben Petrovski; Lisa Wood; Justin D. Brookes (Water Research, 2025)

Scale of unregulated international trade in Australian reptiles and amphibians - Sebastian Chekunov; Oliver Stringham; Adam Toomes; Thomas Prowse; Phillip Cassey (Conservation Biology, 2024)
Reptiles and amphibians are popular in the exotic pet trade, where Australian species are valued for their rarity and uniqueness. Despite a near‐complete ban on the export of Australian wildlife, smuggling and subsequent international trade frequently occur in an unregulated and unmonitored manner. In 2022, Australia listed over 100 squamates in Appendix III of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) to better monitor this trade. We investigated current trade and assessed the value of this Australian CITES listing using web‐scraping methods to monitor the online pet trade in Australian reptiles and amphibians, with additional data from published papers, trade databases, and seizure records. Despite the export ban, we identified 170 endemic herpetofauna (reptile and amphibian) species in international trade, 33 of which were not recorded previously in the international market, including 6 newly recorded genera. Ninety‐two traded species were included in CITES appendices (59 added in 2022), but at least 78 other traded species remained unregulated. Among these, 5 of the 10 traded threatened species were unlisted, and we recommend they be considered for inclusion in CITES Appendix III. We also recommend the listing of all Diplodactylidae genera in Appendix III. Despite this family representing the greatest number of Australian species in trade, only one genus (of 7 traded) was included in the recent CITES amendments. Overall, a large number of Australian reptile and amphibian species are traded internationally and, although we acknowledge the value of Australia's recent CITES listing, we recommend the consideration of other taxa for similar inclusion in CITES.

Forecasting potential invaders to prevent future biological invasions worldwide - Arman N. Pili; Boris Leroy; John G. Measey; Jules E. Farquhar; Adam Toomes; Phillip Cassey; Sebastian Chekunov; Matthias Grenié; Dylan van Winkel; Lisa Maria; Mae Lowe L. Diesmos; Arvin C. Diesmos; et al. (Global Change Biology, 2024)
The ever‐increasing and expanding globalisation of trade and transport underpins the escalating global problem of biological invasions. Developing biosecurity infrastructures is crucial to anticipate and prevent the transport and introduction of invasive alien species. Still, robust and defensible forecasts of potential invaders are rare, especially for species without known invasion history. Here, we aim to support decision‐making by developing a quantitative invasion risk assessment tool based on invasion syndromes (i.e., generalising typical attributes of invasive alien species). We implemented a workflow based on ‘Multiple Imputation with Chain Equation’ to estimate invasion syndromes from imputed datasets of species' life‐history and ecological traits and macroecological patterns. Importantly, our models disentangle the factors explaining (i) transport and introduction and (ii) establishment. We showcase our tool by modelling the invasion syndromes of 466 amphibians and reptile species with invasion history. Then, we project these models to amphibians and reptiles worldwide (16,236 species [c.76% global coverage]) to identify species with a risk of being unintentionally transported and introduced, and risk of establishing alien populations. Our invasion syndrome models showed high predictive accuracy with a good balance between specificity and generality. Unintentionally transported and introduced species tend to be common and thrive well in human‐disturbed habitats. In contrast, those with established alien populations tend to be large‐sized, are habitat generalists, thrive well in human‐disturbed habitats, and have large native geographic ranges. We forecast that 160 amphibians and reptiles without known invasion history could be unintentionally transported and introduced in the future. Among them, 57 species have a high risk of establishing alien populations. Our reliable, reproducible, transferable, statistically robust and scientifically defensible quantitative invasion risk assessment tool is a significant new addition to the suite of decision‐support tools needed for developing a future‐proof preventative biosecurity globally.

Who’s a pretty bird? Predicting the traded abundance of bird species in Australian online pet trade - Katherine G. W. Hill; Oliver C. Stringham; Stephanie Moncayo; Adam Toomes; Jonathan J. Tyler; Phillip Cassey; Steven Delean (Biological Invasions, 2024)

A snapshot of online wildlife trade: Australian e-commerce trade of native and non-native pets - Adam Toomes; Stephanie Moncayo; Oliver C. Stringham; Charlotte Lassaline; Lisa Wood; Mariah Millington; Charlotte Drake; Charlotte Jense; Ashley Allen; Katherine G.W. Hill; Pablo García-Díaz; Lewis Mitchell; et al. (Biological Conservation, 2023)

A guide to using the internet to monitor and quantify the wildlife trade - Oliver C. Stringham; Adam Toomes; Aurelie M. Kanishka; Lewis Mitchell; Sarah Heinrich; Joshua V. Ross; Phillip Cassey (Conservation Biology, 2021)
The unrivaled growth in e‐commerce of animals and plants presents an unprecedented opportunity to monitor wildlife trade to inform conservation, biosecurity, and law enforcement. Using the internet to quantify the scale of the wildlife trade (volume and frequency) is a relatively recent and rapidly developing approach that lacks an accessible framework for locating relevant websites and collecting data. We produced an accessible guide for internet‐based wildlife trade surveillance. We detailed a repeatable method involving a systematic internet search, with search engines, to locate relevant websites and content. For data collection, we highlight web‐scraping technology as an efficient way to collect data in an automated fashion at regularly timed intervals. Our guide is applicable to the multitude of trade‐based contexts because researchers can tailor search keywords for specific taxa or derived products and locations of interest. We provide information for working with the diversity of websites used in wildlife trade. For example, to locate relevant content on social media (e.g., posts or groups), each social media platform should be examined individually via the site's internal search engine. A key advantage of using the internet to study wildlife trade is the relative ease of access to an increasing amount of trade‐related data. However, not all wildlife trade occurs online and it may occur on unobservable sections of the internet.